New records of giant butterfly-moths (Lepidoptera: Castniidae) from Colombia with general notes on natural history - HERNÁNDEZ-BAZ, FERNANDO; SERNA, FRANCISCO; VERGARA NAVARRO, ERIKA V.; LAMAS, GERARDO; GONZÁLEZ, JORGE M. (Revista Colombiana de Entomología, 2012)
Eupalamides cyparissias amazonensis and an intermediate phenotype of two ssp. of Duboisvalia simulans are reported for the first time from Colombia based on the discovery of one specimen each present in two collections of the country. Besides their relevance for increasing the geographical distribution of both taxa, additional information is provided.